The efficacy and safety of adding on or switching to peginterferon α‐2b in HBeAg‐positive chronic hepatitis B patients with long‐term entecavir treatment: a multicentre randomised controlled trial. Issue 9 (20th September 2022) - Hu, Qiankun; Qi, Xun; Yu, Yiqi; Gao, Yueqiu; Zhang, Xinxin; Wang, Qianqian; Zhang, Xueyun; Zhuo, Yunhui; Li, Jing; Zhang, Jiming; Chen, Liang; Huang, Yuxian
Summary: Background & Aims: The strategies of adding on or switching to peginterferon (PEG‐IFN) improved the serological response rates in patients with chronic hepatitis B (CHB) who had previously experienced treatment with nucleos(t)ide analogues. However, robust data on which combination strategy is more effective remain lacking. Methods: In this multicentre, parallel, open‐label, randomised, controlled trial, patients with HBeAg‐positive CHB who were treated with entecavir ≥2 years, and had hepatitis B surface antigen (HBsAg) <3000 IU/ml, HBeAg <200S/CO and HBV DNA <50 IU/ml were randomly assigned in a 1:1:1 ratio to add on PEG‐IFN, switch to PEG‐IFN or continue entecavir monotherapy for 48 weeks. The primary endpoint was HBeAg seroconversion at week 48. Results: A total of 153 patients were randomised into three treatment arms (50 in add‐on, 52 in switch‐to and 51 in monotherapy). Compared with continuous entecavir monotherapy, both add‐on and switch‐to strategies achieved higher rates of HBeAg seroconversion (18.0% vs. 2.0%, p  = 0.007; 19.2% vs. 2.0%, p  = 0.005, respectively), HBeAg loss (24.0% vs. 5.9%, p  = 0.010; 23.1% vs. 5.9%, p  = 0.013, respectively), HBsAg < 100 IU/ml (30.0% vs. 0%, p  < 0.001; 34.6% vs. 0%, p  < 0.001, respectively), and higher HBsAg reduction (−0.90 vs. −0.06 log10 IU/ml, p  < 0.001; −0.92 vs. −0.06 log10 IU/ml, p  < 0.001, respectively) at week 48. The efficacy was comparable between add‐on and switch‐to arms ( p >  0.05). Adverse events were mainly related to PEG‐IFN but generally tolerable. Conclusion: In patients with CHB who achieved virological response with long‐term entecavir, both adding on and switching to PEG‐IFN are alternative strategies resulting in higher rates of HBeAg seroconversion and HBsAg reduction than continuous entecavir. Clinical trials registration: Chinese Clinical Trial Registry (www.chictr.org.cn, identifier: ChiCTR‐IPR‐17012055). Abstract : The efficacy and safety of adding on or switching to peginterferon α‐2b in HBeAg‐positive chronic hepatitis B patients with long‐term entecavir treatment: a multicentre randomised controlled trial.